Portfolio Management and Performance of Deposit Money Banks in Nigeria (1990–2020) (2025)
There have been a renewed focus on portfolio management of deposit money banks since the global financial crisis of 2007–09. This renewed focus is based on the understanding that an efficient portfolio management reduces risks and loss associated with uncertainty of investment returns which may impact on the performance of banks. In this study, we investigated the connection between portfolio management and performance of deposit money banks in Nigeria. The study essentially sought to ascertain whether portfolio management has predictive value for the out-of-sample predictability of profitability of deposit money banks in Nigeria. The Markowitz portfolio theory underpin the study while time series data on deposit money banks’ liquidity, financial assets, foreign portfolio asset, deposit mix, and private sector concentration were utilized for the analysis. The time series spanned from 1990 to 2020 based on data availability. To increase the robustness of the result, the entire 24 DMBs were included in the study. The unit root test and bound cointegration test were employed to check times series behaviour of the variables. The Autoregressive Distributed Lag (ARDL) was used to estimate both the short-run and long-run dynamics and rapid correction to long-run equilibrium. Our findings reveal that portfolio management and its variants had significant effect on the profit after tax (PAT), return on investment (ROI), asset quality (ASQ), and capital adequacy (CA) of deposit money banks in Nigeria.